2015
DOI: 10.1039/c5ta06012e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and fluorine co-doped graphene as a high-performance anode material for lithium-ion batteries

Abstract: Supplementary InformaƟon (ESI) available: FT-IR spectrum, Raman spectrum, XRD patterns, XPS survey spectra, TEM and SEM images, the first three CV curves, Cycle performance, and rate capabilities of NG and RGO See Nitrogen and fluorine co-doped graphene (NFG) with the N and F content as high as 3.24 and 10.9 at.% was prepared through the hydrothermal reaction of trimethylamine tri(hydrofluoride) [(C2H5)3N·3HF] and aqueous-dispersed graphene oxide (GO) as the anode material for lithium ion batteries (LIBs). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(106 citation statements)
references
References 87 publications
3
101
0
2
Order By: Relevance
“…They correspond to surface F at different densities. It has also been reported that these peaks are attributed to semi‐ionic (F LD −C) and covalent (F HD −C) C−F bonding . An additional peak is found in the FMX3 spectrum at a higher BE of 689.4 eV attributed to CF 2 as is also seen from the C 1s spectrum (see Figure a) .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…They correspond to surface F at different densities. It has also been reported that these peaks are attributed to semi‐ionic (F LD −C) and covalent (F HD −C) C−F bonding . An additional peak is found in the FMX3 spectrum at a higher BE of 689.4 eV attributed to CF 2 as is also seen from the C 1s spectrum (see Figure a) .…”
Section: Resultssupporting
confidence: 86%
“…The spectrum from the FMX24 sample shows only two peaks that are related to Ti−O−F bonds and covalently bonded F with a high surface coverage. With higher fluorination times it is confirmed that the samples start to be dominated by two types of F, the Ti−O−F bond and densely packed covalently bonded F (F HD −C) …”
Section: Resultsmentioning
confidence: 67%
“…A clear difference in the diffraction patterns is observed for those recorded from the rGO (edges) as well as from the phosphor regions (inner region) of the rGO wrapped phosphor particles. The SAED pattern recorded from the inner regions correspond to the phosphor21 while the SAED pattern recorded from edges correspond to rGO222324.…”
Section: Resultsmentioning
confidence: 99%
“…Other kinds of graphene also proved their strength upon long term cycling. Indeed, N-doped RGO, [ 95 ] porous RGO aerogel, [ 96 ] N-doped 3D macroporous RGO, [ 97 ] N-doped graphene (synthesized by bottom-up procedure), [ 98 ] N-S-codoped RGO, [ 99 ] N-F-codoped RGO, [ 100 ] N-doped holey RGO foam, [ 101 ] and porous graphene (obtained by a peculiar top-down process) [ 102 ] displayed some of the most promising electrochemical performances among all graphene-based anodes (Table 1 ). Interestingly, it was also proved that multilayer graphene (obtained by liquid-phase exfoliation in 1-ethyl-3-methylimidazolium acetate ionic liquid) could reversibly store lithium ions down to −30 °C, showing noticeable specifi c gravimetric capacity even when directly compared to its graphite analogue.…”
Section: Continuedmentioning
confidence: 99%